2021
DOI: 10.1080/19490976.2021.1946368
|View full text |Cite
|
Sign up to set email alerts
|

Chronic opioid use modulates human enteric microbiota and intestinal barrier integrity

Abstract: Over the past three decades the United States has experienced a devastating opioid epidemic. One of the many debilitating side effects of chronic opioid use is opioid-induced bowel dysfunction. We investigated the impact of methadone maintenance treatment (MMT) on the gut microbiome, the gut bacterial metabolite profile, and intestinal barrier integrity. An imbalance in key bacterial communities required for production of short-chain fatty acids (SCFAs), mucus degradation, and maintenance of barrier integrity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 62 publications
3
40
1
Order By: Relevance
“…Furthermore, it is worth noting that the reconstitution of intestinal microbiota biofilm [ 63 , 64 ] is another important pathophysiological feature of H 2 S. Therefore, we postulate that the reversion of gut dysbiosis exerted by H 2 S might also contribute to their analgesic effects. Furthermore, the co-administration of low doses of H 2 S donors and opioids might also avoid the dysbiosis [ 51 ] and bacterial translocation [ 65 , 66 ] induced by high doses of opioids, thus maintaining the homeostasis of gut microbiota. Nevertheless, further studies are needed to demonstrate this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is worth noting that the reconstitution of intestinal microbiota biofilm [ 63 , 64 ] is another important pathophysiological feature of H 2 S. Therefore, we postulate that the reversion of gut dysbiosis exerted by H 2 S might also contribute to their analgesic effects. Furthermore, the co-administration of low doses of H 2 S donors and opioids might also avoid the dysbiosis [ 51 ] and bacterial translocation [ 65 , 66 ] induced by high doses of opioids, thus maintaining the homeostasis of gut microbiota. Nevertheless, further studies are needed to demonstrate this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Gut microbiota and gut-brain communication also play a critical role in opioid use and opioid tolerance [ 85 , 86 ]. Chronic opioid use alters fecal microbial diversity and composition and induces gut microbial dysbiosis in both rodents and humans, accompanied by increases in peripheral and central inflammation [ 87 89 ]. Moreover, microbial metabolites, such as short-chain fatty acids, are reduced, and intestinal and blood-brain barrier integrity is disrupted after opioid use, which could modulate the development, maturation, and function of microglia and exacerbate the neuroimmune responses [ 87 , 89 , 90 ].…”
Section: Neuroinflammationmentioning
confidence: 99%
“…Chronic opioid use alters fecal microbial diversity and composition and induces gut microbial dysbiosis in both rodents and humans, accompanied by increases in peripheral and central inflammation [ 87 89 ]. Moreover, microbial metabolites, such as short-chain fatty acids, are reduced, and intestinal and blood-brain barrier integrity is disrupted after opioid use, which could modulate the development, maturation, and function of microglia and exacerbate the neuroimmune responses [ 87 , 89 , 90 ]. Neuroinflammation that is induced by alterations of the microbiota can ultimately contribute to behaviors that are associated with opioid dependence [ 91 , 92 ].…”
Section: Neuroinflammationmentioning
confidence: 99%
“…Opioid use has also been shown to increase susceptibility to several pathogenic infections, including Pseudomonas aeruginosa, Enterococcus faecalis , and Listeria monocytogenes , thereby predisposing toward sepsis and immune dysregulation ( 90 94 ). A recent clinical study identified an enrichment of family Bifidobacteriaceae and depletion of Akkermansiaceae among opioid users, along with a significant reduction in fecal SCFA levels ( 95 ). Opioid treatment has also been shown to change the level of bacterial metabolites.…”
Section: Gut Microbial Alterations In Oud and Sars-cov-2 Infectionmentioning
confidence: 99%